Using Peers in Instructional Development - Mikula, Alan R. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Peer observation is discussed as an aid in instructional development, rather than a method for teacher evaluation. A team effort, consisting of from three to four peers who observe each other from four to seven times during the span of one term offers the greatest likelihood that instruction will be improved. Whether these groups are elective or assigned, disciplinary or interdisciplinary, is a matter of institutional preference and each combination offers unique advantages. Instructing faculty members in the terminology, philosophy, and methodologies of observing the teaching/learning process is crucial, and the orientation sessions require an introduction to the educational jargon used in observation. An orientation, or pre-observation conference can allow the observee to provide the team with his objectives for the lesson they are to observe and the criteria for the observation. Observation in the classroom should be unobtrusive. In a post-observation conference the observee analyzes the achievement of the lesson objectives, and the team provides feedback based on their data sheets. Based on the discussion, the observee can plan to increase some behaviors, such as questioning, or maintain the use of techniques which were successful. Evaluation of the effectiveness of a peer observation program is discussed. (SW)
ERIC Note: Paper presented at the conference on Faculty Development and Evaluation in Higher Education (Orlando, Florida, 1979).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Observation Techniques; College Faculty; Faculty College Relationship; Faculty Development; Faculty Evaluation; Higher Education; Instructional Improvement; Observation; Peer Evaluation; Teacher Effectiveness; Information Analyses; Speeches/Meeting Papers